Phosphorus recovery as struvite from farm, municipal and industrial waste: feedstock suitability, methods and pre-treatments - Kataki, Sampriti; West, Helen M.; Clarke, Michèle L.; Baruah, Debendra C. (Elsevier, 2016)
Global population growth requires intensification of agriculture, for which a sustainable supply of phosphorus (P) is essential. Since natural P reserves are diminishing, recovering P from wastes and residues is an increasingly attractive prospect, particularly as technical and economic potential in the area is growing. In addition to providing phosphorus for agricultural use, precipitation of P from waste residues and effluents lessens their nutrient loading prior to disposal. This paper critically reviews published methods for P recovery from waste streams (municipal, farm and industrial) with emphasis on struvite (MgNH4PO46H2O) crystallisation, including pre-treatments to maximise recovery. Based on compositional parameters of a range of wastes, a Feedstock Suitability Index (FSI) was developed as a guide to inform researchers and operators of the relative potential for struvite production from each waste.